Random Statistical Analysis of Transverse Momentum Spectra of Strange Particles and Dependence of Related Parameters on Centrality in High Energy Collisions at the LHC - Xu-Hong Zhang; Fu-Hu Liu; Khusniddin K. Olimov; Airton Deppman (Advances in High Energy Physics)
We have studied the transverse momentum (pT) spectra of the final-state strange particles, including K±, ϕ, Ξ, and Ω, produced in high energy lead–lead (Pb–Pb), proton–lead (p–Pb), xenon–xenon (Xe–Xe) collisions at the Large Hadron Collider (LHC). Taking into account the contribution of multiquark composition, whose probability density distribution is described by the modified Tsallis–Pareto-type function; we simulate the pT spectra of the final-state strange particles by a Monte Carlo method, which is shown to be in good agreement with the experimental data in most the cases. The kinetic freeze-out parameters are obtained. The present method provides a new tool for studying the spectra of various particles produced in high energy collisions, reflecting more realistically the collision process, which is of great significance to study the formation and properties of the produced particles.